Cross-Cultural Leader Development in a University Club: An Autoethnography - Jason Edward Lewis (Educational Process: International Journal)
There is a growing body of research on the organization, effectiveness, and strategies of leadership teams. Less research exists on such aspects in cross-cultural teams. Little is known about how team leadership can be used in cross-cultural university clubs and how such settings foster leader development. Within the framework of existing literature, this analytic autoethnography examines how I develop leadership skills in university students cross-culturally through a student choir club by utilizing a team leadership model. This study provides an understanding of how leader development can occur in university clubs in cross-cultural settings through employing a team leadership model. Student club advisors may benefit from knowing the benefits of consciously developing leadership skills with club members and some strategies of how to develop such skills. Students might recognize the advantages of clubs that can help them become better leaders. Current club leaders can see that leadership skills can be developed in all types of clubs, especially within a choir. University administrators can see the practical value of extra-curricular student clubs in developing leaders.